Software Engineering and Filmmaking: A Literature Review - Farina, Mirko; Fedorovskaya, Arina; Polivtsev, Egor; Succi, Giancarlo (Frontiers in Computer Science, 2022)
Software development is a complex process that requires skills in mathematics and physics. Moreover, it usually includes collaboration with other people. To get a precise understanding of the way such a process is organised, we need to understand its essence. Technical knowledge is crucially important for any developer; however, another important characteristic of any software engineer is creativity. In this paper, we look at one particular artistic practice [filmmaking] that involves both these latter characteristics to determine whether insights from such a practice can be applied in the IT industry and vice versa.